Impact of different definitions of atopic dermatitis. (3rd December 2019) - Nakamura, T.; Haider, S.; Colicino, S.; Murray, C.S.; Holloway, J.; Simpson, A.; Cullinan, P.; Custovic, A.; ,
Summary: Atopic dermatitis (AD) is one of the most common skin diseases, but there is no single term used to define this illness. Although AD is currently the most commonly used name for this condition, other names (such as eczema) are also common. This may make it difficult to compare the results between studies and to understand the true burden of the disease. We found that researchers in different countries and different medical specialties used different names (AD or eczema), but that these two names do not always relate to the same illness. We then investigated whether researchers would find different results and draw different conclusions if they used the same name (AD), but defined it in a slightly different way in their studies. To do this, we first reviewed medical literature to find the most common ways researchers defined AD. We found a staggering 59 different definitions of AD in 45 studies which we reviewed. We then selected four definitions which were most commonly used and applied them to >1000 children in two birth cohorts (they were born in the same set time period) from the UK. Using these different definitions resulted in a major difference in the number of children labelled as having AD (so called prevalence of the disease), as well as differences in the evaluation of the importance of genes and other risk factors for the disease. The authors conclude that a common and universally accepted definition of this disease is urgently needed, in order to fully appreciate its impact on patients, their families and society, and to identify how important various genes and environmental exposures are. Abstract : Linked Article:  Nakamura et al. Br J Dermatol 2019; 181 :1272–1279